Defects in Laterality with Emphasis on Heterotaxy Syndromes with Asplenia and Polysplenia: An Autopsy Case Series at a Single Institution. (July 2014) - Burton, Elizabeth C.; Olson, Michelle; Rooper, Lisa
Heterotaxy is a rare disease with high morbidity and mortality. Controversy exists over how to classify these syndromes with most cases stratified into asplenia/polysplenia syndromes or right/left isomerism. In an effort to review comprehensively specific pheonotypes associated with heterotaxy syndromes, we reviewed published cases series, adopted a classification scheme based on spleen status, and evaluated autopsy cases retrospectively with abnormal laterality at our institution. We categorized 116 cases as situs inversus totalis, polysplenia, asplenia, and single right-sided spleen. Cardiovascular abnormalities occurred in 87.1% of polysplenia, 90.5% of asplenia, and all cases of single right-sided spleen. For polysplenia, 48.9% had bilateral bilobed lungs, 87% had right-sided stomach, 58.1% had midline symmetric liver, and 60.4% had malrotated intestines. For asplenia, 51.9% had bilateral trilobed lungs, 86.7% had right-sided stomach, 45.8% had symmetric liver, and 65.5% had malrotated intestines. Atrioventricular septal defects occurred in 91.2% of asplenia compared to 56.8% of polysplenia cases. Eight percent had pulmonary/aortic stenosis or atresia. Double outlet right ventricle was more common in polysplenia (32.6%) compared to asplenia (21.4%). Total anomalous systemic venous return was described in 55.6% of polysplenia and total anomalous pulmonary venous connections in 81% of asplenia cases. Greater than half of the cases had no heterotaxy diagnosis. Although, we found similar heterotaxy-associated characteristics, the frequencies differed from previous studies. We found great variation in how heterotaxy-associated defects were described, diagnosed, and reported. Although there are known associated characteristics with the polysplenia/asplenia syndromes, correct identification requires a standardized approach for diagnosis and reporting.